Evaluation of selected tropical marine microalgal cultures for use in biophotovoltaic platforms / Tay Hui Yee Zoe - Tay , Hui Yee Zoe (2022)
Microalgal-Biophotovoltaic (BPV) research is an emerging discipline in the field of renewable solar energy technology. When exposed to light, microalgae in BPV platforms will use their photosynthetic apparatus to carry out a water splitting reaction which forms oxygen, protons and electrons. The electrons will then be harvested through the anode of a BPV platform to generate electricity. At the same time, carbon dioxide is also consumed by the microalgae which presents the BPV platform as a means to deliver carbon-neutral or carbon-negative energy. In this study, the bioelectrical power generation potential of four tropical marine microalgal strains were investigated through the use of BPV platforms since no known study has investigated on this particular group of marine microalgae to date. Using controlled laboratory experiments, the bioelectrical power outputs of the chlorophytes Parachlorella UMACC 245 and Chlorella UMACC 258, diatom Halamphora subtropica UMACC 370, and cyanobacterium Synechococcus UMACC 371 were determined. Chlorella UMACC 258 was able to produce the highest power density (0.108 mW m-2), followed by Halamphora subtropica UMACC 370 (0.090 mW m-2), Synechococcus UMACC 371 (0.065 mW m-2) and Parachlorella UMACC 245 (0.017 mW m-2). The chlorophyll-a content was examined to have a linear positive relationship with the power density (p < 0.05). Using the Pulse-Amplitude Modulation (PAM) fluorometer, the photosynthetic performance (maximum quantum efficiency, Fv/Fm) of the algal cultures was studied by exposure to a range of actinic irradiances in order to determine their cell physiological stress from photosynthesis. Other parameters of the photosynthetic performance including the alpha (α), maximum relative electron transport rate (rETRmax), photo-adaptive index (Ek) and non-photochemical quenching (NPQ) were also investigated. The Fv/Fm values of all strains, with the exception of Synechococcus UMACC 371, were within a relatively healthy range of 0.37 to 0.50 on the day when power output was greatest before declining by the end of the experiment likely due to nutrient depletion. Synechococcus UMACC 371 produced Fv/Fm values less than 0.30 and this was possibly caused by the presence of background fluorescence from phycobilisomes or phycobiliproteins. The NPQ, which measures the ability of the microalgae to dissipate excess energy as heat in order to induce photoprotection, was strongest in Halamphora subtropica UMACC 370 and weakest in Synechococcus UMACC 371. NPQ activity in Halamphora subtropica UMACC 370 was mediated by its light-harvesting stress-related complex (LHSCR) proteins and extensive de-epoxidation of carotenoids, whereas Synechococcus UMACC 371 employed the Orange Carotenoid Protein (OCP) associated with phycobilisomes. Electrochemical studies via cyclic voltammetry suggest the presence of electro-active proteins on the cellular surface of strains on the carbon anode of the BPV platform, while morphological studies via FESEM imaging verifies the biocompatibility of the biofilms on the carbon anode.